Implementasi Program Daily Activity Menggunakan Kata Ajaib dalam Pembentukan Karakter Sopan Santun Kelompok B1 TK Pertiwi Sowankidul - Nisa, Rohmatun; Wiranti, Dwiana Asih (Indo-MathEdu Intellectuals Journal, 2024)
Character education is one of the most important things that young children should get as 80% of their brain development occurs during that time. A lack of respect and regard for others might be influenced by the absence of character education in early life. One of the key institutions in helping kids develop their character is their school, and instructors there have a significant influence on how kids behave. The purpose of this study is to explain how a daily activity program that uses magic words to develop polite character is implemented. This study employs a case study methodology and a qualitative research strategy. Interviews and observation were the research methods employed in this study. According to the study's findings, kids are becoming more aware of the usage of "magic words" (sorry, please, thank you, and excuse me) and their conduct is changing as a result. After executing the daily activity program that uses magic words in the construction of polite character, children who had not previously understood the value of utilizing them in everyday life to create polite character now understand it better and are able to use it in their daily lives.